Pharmaceutical Co-crystals: A Review on its Physico-chemical Properties and Role in the Management of Cancer - Manoleena Sarkar; Rajnandan Borah; Rajat Das; Pallab Ghosh; Chandrika Sharma; Jyochhana Priya Mohanty (Krupanidhi College of Pharmacy, 2024)
Academic and industry researchers are becoming more interested in pharmaceutical cocrystals as they emerge as a new class of solid pharmaceuticals with enhanced physico-chemical features. Pharmaceutical co-crystal formation is a simple method for significantly altering a therapeutic substance's solid-state characteristics namely its solubility and consequently bioavailability. A drug's physico-chemical properties can be adjusted by a cocrystal between an active pharmaceutical ingredient (API) and co-former without altering the drug's molecular structure. Numerous types of co-crystals, nano co-crystals and co-crystal-loaded nanocarriers have shown significant promise in the fight against cancer through enhanced pharmacokinetic capabilities, decreased toxicities and improved physico-chemical properties. In this review the physico-chemical properties of co-crystals along with its impact in management of cancer have been demonstrated. Keywords Co-Crystals, Physicochemical, Co-Former, Bioavailability, Nanocarriers